ACOMPANHAMENTO PERIOPERATÓRIO: PACIENTE SUBMETIDA À CIRURGIA DE CÂNCER DE ASSOALHO DE BÔCA - Kusiack, Adriana; Stumm, Eniva M. F.; Wink, Carla; Kitzmann, Thiély S. (Salão do Conhecimento, 2013)
Resumo